2013
DOI: 10.1074/jbc.m112.426205
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation-sensing Regulator AbfR Regulates Oxidative Stress Responses, Bacterial Aggregation, and Biofilm Formation in Staphylococcus epidermidis

Abstract: Background: Staphylococcus epidermidis senses and responds to oxidative stress through an unknown mechanism. Results: The paper describes AbfR, the first oxidation sensor of S. epidermidis. Conclusion: AbfR plays key roles in oxidative stress responses, bacterial aggregation, and biofilm formation in S. epidermidis. Significance: Oxidative stress signals S. epidermidis to modulate key virulence properties through AbfR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 65 publications
(16 reference statements)
0
31
0
Order By: Relevance
“…For example, polysaccharide production is known to be linked to biofilms in Staphylococcus , Pseudomonas and Campylobacter (Joshua et al ., ; Rohde et al ., ; Ghafoor et al ., ; Spiliopoulou et al ., ). Links with oxidative stress have been observed with biofilm formation in Campylobacter (Fields and Thompson, ; Oh and Jeon, ), Yersinia (Bobrov et al ., ), Staphylococcus (Liu et al ., ) and Helicobacter (Barnard et al ., ). However, this is not always the case and, as with some other complex multigene functions, convergent phenotypes can be achieved through divergent genetic changes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, polysaccharide production is known to be linked to biofilms in Staphylococcus , Pseudomonas and Campylobacter (Joshua et al ., ; Rohde et al ., ; Ghafoor et al ., ; Spiliopoulou et al ., ). Links with oxidative stress have been observed with biofilm formation in Campylobacter (Fields and Thompson, ; Oh and Jeon, ), Yersinia (Bobrov et al ., ), Staphylococcus (Liu et al ., ) and Helicobacter (Barnard et al ., ). However, this is not always the case and, as with some other complex multigene functions, convergent phenotypes can be achieved through divergent genetic changes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, notable difference can be observed in the metabolic profiles of biofilms that are cultivated under normoxia versus anoxia . In Staphylococcus epidermidis , the oxidation‐sensing regulator, AbfR (aggregation and biofilm formation regulator) is responsible for the oxidative stress response and its mutant showed enhanced bacterial aggregation, but reduced biofilm formation . Culturing Streptococcus mutans under aerated conditions reduces biofilm formation and oxygen availability results in variations in bacterial cell surface composition and production of autolysins .…”
Section: Role Of Temperature Oxygen and Osmotic Conditions In Biofimentioning
confidence: 99%
“…Furthermore, excessive levels of ROS due to tissue damage create an environment that can serve as an inviting substrate for bacteria to thrive upon. The relationship between exacerbated levels of ROS and bacteria has been reported previously [76] , [77] . Studies have suggested that DNA double-stranded breaks in bacteria caused by oxidative stress lead to mutagenic repair via DNA repair protein RecA, rendering the variants with increased antibiotic resistance and adaptability to the surrounding microenvironment [76] .…”
Section: Discussionmentioning
confidence: 57%
“…Studies have suggested that DNA double-stranded breaks in bacteria caused by oxidative stress lead to mutagenic repair via DNA repair protein RecA, rendering the variants with increased antibiotic resistance and adaptability to the surrounding microenvironment [76] . Furthermore, during excessive oxidative stress, these bacteria upregulate genes that increase their virulence [77] . In an effort to obtain excessive and persistent levels of oxidative stress, we manipulated the early wound microenvironment by inhibiting catalase [78] and GPx activities [79] and introduced our previously isolated S. epidermidis bacterial strain.…”
Section: Discussionmentioning
confidence: 99%